THE HISTORY OF THE EDUCATION OF BODIES IN IBEROAMERICA: REFLECTIONS ON A SUBJECT UNDER CONSTRUCTION - Moro, Paola; Galak, Eduardo; Scharagrodsky, Pablo; Taborda de Oliveira, Marcus (Historia y Memoria de la Educación, 2024)
This article proposes to develop an analyzes of the advances in the history of the bodies education in the last decades in the Ibero-American context. For this, the works presented in the different Ibero-American Congresses of the History of Latin American Education (CIHELA) on this subject are studied, especially from a rereading of the productions written in book format that emerged from them. This analysis is not intended to be exhaustive of the production, but rather to produce a general picture that can serve as a basis for new studies, which identifies recurring themes and vacant areas, an especially relevant issue when considering a transnational research agenda. In this way, the academic productions on the history of the education of the bodies in the CIHELA of Buenos Aires 2007 (VIII), Rio de Janeiro 2009 (IX), Toluca 2014 (XI), Montevideo 2018 (XIII) and Lisbon 2021 are analyzed. (XIV). Through this mapping, the thematic and generational renewal of researchers is observed, the recurrences in the problems and the absent themes, the theoretical references used, as well as the consolidation of an academic field of history of body education in Latin America.